Rheumatic immune-related adverse events secondary to anti–programmed death-1 antibodies and preliminary analysis on the impact of corticosteroids on anti-tumour response: A case series. (December 2018) - Mitchell, Emma L.; Lau, Peter Kar Han; Khoo, Chloe; Liew, David; Leung, Jessica; Liu, Bonnia; Rischin, Adam; Frauman, Albert G.; Kee, Damien; Smith, Kortnye; Brady, Benjamin; Rischin, Danny; et al.
Abstract: Importance: Rheumatic immune-related adverse events (irAEs) occur in approximately 10–20% of anti–programmed death 1 (anti-PD1)–treated cancer patients. There are limited data on the natural history, optimal treatment and long-term oncological outcomes of patients with rheumatic irAEs. Objective: The objective of the study was to describe the spectrum and natural history of rheumatic irAEs and the potential impact of rheumatic irAEs and immunomodulators on anti-PD1 tumour efficacy. Methods: Cancer patients with pre-existing rheumatic disease before anti-PD1 therapy or de novo rheumatic irAEs on anti-PD1 therapy were retrospectively reviewed across three sites. Patient demographics, treatment history, anti-PD1 irAEs, and anti-PD1 responses were evaluated. Relationships between the development or pre-existence of rheumatic irAE, use of immunomodulatory agents and outcomes were evaluated. Results: This multicenter case series describes 36 cancer patients who had rheumatic disease before anti-PD1 therapy (n = 12) or developed de novo rheumatic irAEs (n = 24). Thirty-four of the 36 patients sustained rheumatic irAEs (median time to rheumatic irAE: 14.5 weeks), including 24 de novo (18 inflammatory arthritis, three myositis, two polymyalgia rheumatica, one fasciitis) and 10 flares in 12 patients with pre-existing rheumatic disease. Corticosteroids were used in 30 of 36 patients (median duration: 10 months), and disease-modifying antirheumatic drugs were used in 14 of 36 patients (median duration: 5.5 months). The objective response rate to anti-PD1 therapy was 69% (n = 25/36) overall and 81% (n = 21/26) in the melanoma subgroup. Conclusions: Rheumatic irAEs are often chronic and require prolonged immunomodulatory therapy. Prospective studies are required to define optimal management of rheumatic irAEs that maintain long-term anticancer outcomes. Highlights: Management of anti-PD1 related rheumatic adverse events are less well described compared with other organ specific irAEs. The chronic nature of rheumatic irAE can impact the quality of life and usually requires protracted immunomodulatory agents for management. Patients who sustain a rheumatic irAE secondary to anti-PD1 appear to exhibit higher objective response rates than anticipated.